Time course of arsenic species in red blood cells of acute promyelocytic leukemia (APL) patients treated with single agent arsenic trioxide. Issue 4 (3rd April 2019) - Guo, Meihua; Wang, Bin; Liu, Shuchuan; Wang, Wenjing; Gao, Chunlu; Hu, Shuang; Fan, Shengjin; Hai, Xin; Zhou, Jin
ABSTRACT: Background :Arsenic trioxide (ATO) is widely applied to treat acute promyelocytic leukemia (APL). To elucidate metabolism and toxicity of arsenic, we analyzed time course of arsenic species in red blood cells (RBCs) of APL patients. Methods :Nine APL patients received ATO (0.16 mg/kg/day) through 18-h infusion. Blood was collected before daily administration (days 2 to 9), and at different time points on day 8. Inorganic arsenic (iAs), monomethylarsonic acid (MMA), and dimethylarsinic acid (DMA) were detected by HPLC-ICP-MS. Results :Arsenic species reached Cmax at 18 h on day 8. Arsenicals gradually accumulated during days 2 to 9, whereas their percentages remained almost constant. The general trend in red blood cells (RBCs) was iAs > MMA > DMA. MMA was consistently the predominant methylated arsenic metabolite in RBCs. iAs, MMA, and tAs (tAs = iAs + DMA + MMA) concentrations ( P < 0.0001), MMA/DMA ratios ( P = 0.0016) and iAs% ( P = 0.0013) were higher in RBCs than in plasma. Conclusions :Time course of arsenic species reveal kinetic characteristic of ATO metabolites in RBCs. Arsenic species accumulated with administration frequency. Arsenic species in RBCs were remarkably different from those in plasma. Time course of arsenic species in RBCs is important in ATO clinical application.